Preparation method of two-dimensional Salen-based covalent organic framework lithium-sulfur battery separator with high electronegative groups, separator and lithium-sulfur battery
By combining Salen-TAPT-COF with a two-dimensional Salen-based covalent organic framework material with high electronegative groups with PP, a modified separator is formed, which solves problems such as the polysulfide shuttle effect in lithium-sulfur batteries, and significantly improves the performance and stability of the battery.
Patent Information
- Application Number
- CN202411478290.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-02-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
During the long-term use of lithium-sulfur batteries, there are problems such as polysulfide shuttle effect, low cycle life, capacity attenuation, polarization, safety problems and poor low temperature performance.
Salen-TAPT-COF, a two-dimensional Salen-based covalent organic framework material with high electronegative groups, was prepared by solvothermal method and combined with PP to form a Salen-TAPT-COF/PP modified separator for lithium-sulfur batteries.
The charging and discharge capacity of lithium-sulfur batteries is significantly improved, the stability of the battery is enhanced, the shuttle effect of polysulfide is suppressed, the utilization rate of active substances is improved, and excellent performance in high magnification and long-term stability is shown.
Smart Images

Figure CN119009366B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries, and in particular relates to a preparation method of a two-dimensional Salen-based covalent organic skeleton lithium-sulfur battery diaphragm with high electronegativity groups, a diaphragm and a lithium-sulfur battery. Background Art
[0002] In modern society, human beings' utilization and dependence on fossil fuels have reached an unprecedented level, which has undoubtedly aggravated the severity of environmental problems such as the global greenhouse effect. Therefore, the global demand for potential clean and renewable energy such as wind power and solar energy is increasing, which has greatly promoted the development of efficient and economical energy storage systems. Among them, battery-based energy storage devices are regarded as a key means to achieve large-scale application of renewable energy. Lithium-ion batteries have been widely developed for daily life and production due to their advantages such as high energy density, long life and high operating voltage, and are used in fields such as grid storage, electric vehicles and mobile phones.
[0003] Lithium-sulfur batteries (LSBs) are considered the most promising alternative to lithium-ion batteries for future energy needs due to their high theoretical energy density of 2600 Wh / kg and ultra-high theoretical discharge capacity of 1675 mAh / g. However, despite their many advantages, LSBs still expose a number of problems during long-term use, which are mainly reflected in the following aspects: (1) The "shuttle effect" of polysulfides: During the charge and discharge process, polysulfides (Li2S x , x = 1~8) will dissolve in the electrolyte, causing it to migrate between the positive and negative electrodes. This phenomenon not only reduces the energy efficiency of the battery, but may also cause the battery capacity to decay and cycle stability to decrease; (2) Low cycle life: The cycle life of Li-S batteries is relatively low, that is, the capacity of the battery will gradually decrease during the charge and discharge cycle. (3) Capacity decay: After a period of use, the capacity of Li-S batteries will gradually decay. This is because the reaction products of S during the charge and discharge process will block the electrode pores, resulting in a decrease in battery capacity. (4) Polarization phenomenon: Li-S batteries will experience polarization during the charge and discharge process, that is, the internal resistance of the battery increases, resulting in a decrease in battery performance. (5) Safety issues: Li-S batteries may have safety issues such as thermal runaway and explosion under conditions of overcharge, overdischarge, and high temperature. (6) Poor low temperature performance: Li-S batteries have poor performance in low temperature environments, with faster capacity decay and shorter cycle life.
[0004] In recent years, many methods have been used to inhibit the shuttling effect of polysulfides, including designing and improving sulfur positive electrodes, modifying functional separators, optimizing electrolytes, and protecting lithium negative electrodes. Among them, modifying functional separators is one of the effective ways to improve battery performance. This helps to reduce the loss and shuttling of active materials and improve battery performance. Therefore, modifying the separator is one of the important means to improve the performance of Li-S batteries, extend battery life, and enhance safety. Although traditional polymer separators have good mechanical strength and chemical stability, they have poor conductivity and relatively high cost. Therefore, it is necessary to develop new multifunctional separator materials to improve the performance of lithium-ion batteries. Covalent organic frameworks (COFs) show great potential as electrode materials due to their unique metal-free crystalline organic structure. When used as a modified material for the separator, COF materials can not only provide uniform channels to promote Li + At the same time, it can prevent polysulfides from diffusing from the positive side to the negative side, inhibit the “shuttle effect” of polysulfides, and achieve a long cycle life of LSBs.
[0005] In order to achieve high energy density, researchers have proposed some new design strategies for COF-based membrane modifiers. For example, local polar structures and abundant active sites are obtained by building rich heteroatoms and chemical bonds in the unit. Related reports show that some elements (such as O, N, F, etc.) and chemical bonds (imine, triazine, hydrazone, etc.) can interact with polysulfides through lithium-philic, sulfur-philic or electrostatic interactions, thereby improving the utilization efficiency and cycle stability of sulfur.
[0006] Defects and shortcomings of the existing technology:
[0007] In response to the fatal shortcomings of Li-S batteries, researchers have conducted research in four aspects: sulfur composite cathode structure design, diaphragm modification, electrolyte optimization, and metal lithium anode protection, and have made significant progress. The following are: (1) Development and design of sulfur composite cathode materials. Developing and designing sulfur composite cathodes is a direct and effective means to improve the performance of Li-S batteries. At present, the development of composite sulfur cathodes mainly focuses on carbon / sulfur composite cathodes, metal compound / sulfur composite cathodes, and conductive polymer / sulfur composite cathodes. (2) Design and development of diaphragms.
[0008] Unlike conventional lithium-ion batteries, in Li-S batteries, the separator must not only have +The role of the transport channel is also crucial to inhibit the transport of polysulfides to the negative electrode. In recent years, carbon materials, polymer materials and metal compounds have been widely used in Li-S battery separator coating materials, which effectively inhibit the shuttle of LiPSs and have achieved certain results. (3) Electrolyte optimization. By improving the electrolyte, the energy density and cycle stability of lithium-sulfur batteries can be effectively improved, the internal polarization of the battery can be reduced, the battery life can be extended, and the safety performance of the battery can be improved. (4) Metal lithium negative electrode protection. The long cycle and high safety of the metal lithium negative electrode can be achieved by optimizing the electrolyte, constructing an artificial solid electrolyte interface layer, and designing a separator. However, most of the modification methods involve a multi-step synthesis process, which not only makes the production process more complicated, but also increases the manufacturing cost of the battery. At the same time, after the separator is modified, it may have a certain impact on the lithium and sulfur transport speed, thereby restricting the performance of the battery. Some modifiers can cause problems such as battery safety and stability, such as thermal runaway and short circuit. Summary of the invention
[0009] In view of the problems existing in the prior art, the present application proposes a method for preparing a two-dimensional Salen-based covalent organic framework lithium-sulfur battery separator with high electronegative groups, a separator and a lithium-sulfur battery. The present application designs and prepares a stable ternary porous cationic organic framework, and obtains Salen-TAPT-COF by doping N and O atoms, which has high crystallinity and excellent stability. At the same time, this material is prepared into a Salen-TAPT-COF / PP lithium-sulfur battery modified separator, and studies have shown that it plays a vital role in the shuttling of polysulfides (Li2Sx) in lithium-sulfur batteries.
[0010] The method for preparing the two-dimensional Salen-based covalent organic framework lithium-sulfur battery separator having a high electronegative group comprises the following steps:
[0011] S1. Synthesis of Salen-TAPT-COF
[0012] Weigh 3,3'-((1E,1'E)-(ethane-1,2-diylbis(azoethylene))bis(methaneethylene))bis(4-hydroxybenzaldehyde) (Salen) and 1,3,5-tris(4-aminophenyl)-1,3,5-triazine (TAPT) into a Pyrex tube, add a mixed solvent of 1,2-dichlorobenzene and mesitylene into the Pyrex tube, treat under ultrasonication for 4-5 min, fully mix with the mixed monomers, add a catalyst acetic acid aqueous solution, and continue ultrasonication for 1-5 min; then degas for three cycles in a liquid nitrogen bath using a freeze pump thawing technique, seal the tube under vacuum and heat, cool to room temperature after heating to obtain a light red solid, wash the light red solid with THF 3-4 times, and vacuum dry under dynamic vacuum to obtain a light red powder Salen-TAPT-COF;
[0013] Synthesis of S2. Salen-TAPT-COF / PP
[0014] Salen-TAPT-COF was placed in a ball mill and fully ground for 30 minutes to obtain COF powder; COF powder, Ketjen black and PVDF were mixed and ball-milled for 1-1.5 hours, and finally 1-methyl-2-pyrrolidone (NMP) was added for wet grinding to obtain slurry; the slurry was evenly coated on the surface of the PP diaphragm using a coater, and then vacuum dried to obtain Salen-TAPT-COF / PP lithium-sulfur battery separator.
[0015] The mass ratio of 3,3'-((1E,1'E)-(ethane-1,2-diylbis(azoethylene))bis(methaneethylene))bis(4-hydroxybenzaldehyde) (Salen) and 1,3,5-tris(4-aminophenyl)-1,3,5-triazine (TAPT) in step S1 is (5-10):7;
[0016] The volume ratio of 1,2-dichlorobenzene to mesitylene in step S1 is 1:1;
[0017] The usage ratio of Salen and 1,2-dichlorobenzene in step S1 is (30-45) mg / ml;
[0018] The concentration of the acetic acid aqueous solution in step S1 is 6 mol / L, and the amount of the acetic acid aqueous solution used is 0.2 ml;
[0019] In step S1, the heating temperature is 100-120°C and the heating time is 120-122 h;
[0020] The vacuum drying temperature in step S1 is 80-100°C, and the vacuum drying time is 10-12 h;
[0021] The mass ratio of COF powder, Ketjen black and PVDF in step S2 is 7:2:1;
[0022] The wet grinding time in step S2 is 20-30 min;
[0023] The vacuum drying temperature in step S2 is 50-60°C, and the vacuum drying time is 20-24 h;
[0024] A diaphragm, prepared by the above-mentioned preparation method;
[0025] A lithium-sulfur battery comprises a diaphragm prepared by the above preparation method.
[0026] Compared with the prior art, the present invention has the following advantages:
[0027] 1. A nitrogen-rich and oxygen-rich covalent organic framework Salen-TAPT-COF was prepared by a solvothermal method, which showed good stability and high specific surface area. At the same time, it was prepared into Salen-TAPT-COF / PP modified PP film and applied to lithium-sulfur batteries, which greatly improved the battery's charge and discharge capacity and enhanced the battery's stability.
[0028] 2. The Salen-TAPT-COF modified layer can capture and reuse dissolved polysulfides, while accelerating the transfer of electrons and ions, thereby inhibiting the shuttle effect and improving the utilization of active substances. Typical Salen-TAPT-COF modified membrane LSBs. At 0.1 A·g -1 The lower has 1168.6 mA·h·g -1 The initial discharge capacity is as high as 683.4 mA·h·g at a current density of 2 C. -1 At a current density of 1 C, the capacity retention rate is still 577.7 mA·h·g after 500 cycles. -1 The results showed that Salen-TAPT-COF had good rate performance and reversibility. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 Schematic diagram of the synthesis process of the polymer Salen-TAPT-COF obtained in the present invention;
[0030] Figure 2 The PXRD pattern and FT-IR spectrum of the polymer Salen-TAPT-COF obtained in Example 1 of the present invention are shown in FIG. 13 C NMR spectrum and TGA curve, where Figure 2 (a) is the PXRD spectrum of the polymer Salen-TAPT-COF obtained in the present invention; Figure 2(b) is the FT-IR spectrum of the polymer Salen-TAPT-COF obtained in the present invention and its corresponding monomer; Figure 2 (c) is the polymer Salen-TAPT-COF obtained in the present invention 13 C NMR spectroscopy; Figure 2 (d) is a TGA curve diagram of the polymer Salen-TAPT-COF obtained in the present invention;
[0031] Figure 3 The SEM and EDS images of the polymer Salen-TAPT-COF obtained in Example 1 of the present invention are shown in FIG. Figure 3 (a) is a SEM image of the polymer Salen-TAPT-COF obtained in the present invention; Figure 3 (b) is the EDS graph of the polymer Salen-TAPT-COF obtained in the present invention;
[0032] Figure 4 This is the XPS graph of Salen-TAPT-COF obtained in the present invention;
[0033] Figure 5 is a performance diagram of the Li-S battery prepared in the present invention, wherein: Figure 5 (a) Scan rate 0.1 mV·s -1 CV curves of two different film LSBs; Figure 5 (b) 0.1 A·g -1 Typical charge and discharge curves at current density; Figure 5 (c) Rate cycling performance of LSBs assembled with two different membranes at different current densities. Figure 5 (d) is the charge and discharge curve of Salen-TAPT-COF modified membrane battery at different current densities; Figure 5 (e) is the charge and discharge curve of PP film battery at different current densities; Figure 5 (f) Two different film LSBs at 1 A·g -1 Long-term stability under
[0034] Figure 6 It is the PXRD pattern of the sample of Comparative Example 1;
[0035] Figure 7 It is the PXRD pattern of the sample of Comparative Example 2;
[0036] Figure 8 This is the PXRD pattern of the sample in comparative example 3. DETAILED DESCRIPTION
[0037] The following will clearly and in detail describe the concept and technical effects of the present invention in combination with the embodiments and drawings, so as to fully understand the purpose, features and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.
[0038] The present invention is further described below in conjunction with the embodiments. The instruments and equipment used in the embodiments of the present invention and their models are: Shanghai Chenhua electrochemical workstation (Chenhua CHI660E) and Blue Electric Battery Test System (CT2001A).
[0039] The Li-S battery was measured in the voltage range of 1.7~2.8 V, 0.1 mV·s -1 Cyclic voltammetry curves at . Electrochemical impedance spectroscopy, the cycling stability at 1 C and the rate performance of Li-S batteries at different current densities were measured on a Blue Battery Test System (CT2001A).
[0040] The assembly process of the Li-S battery of the present invention comprises the following steps:
[0041] 1. Preparation of C / S composites
[0042] The C / S composite material was prepared using the traditional melt diffusion method. First, Super-P powder and sulfur powder in a mass ratio of 2:8 were mixed and fully ground in a mortar. Then, the mixture obtained after grinding was placed in a polytetrafluoroethylene-lined reactor and heated at 155 °C for 24 h under an argon protection atmosphere. Finally, the product was collected after cooling to room temperature to obtain a C / S composite material.
[0043] 2. Preparation of conventional positive electrode
[0044] The C / S composite material, carbon black and PVDF were mixed in a mass ratio of 8:1:1 and ground evenly, and then 1-methyl-2-pyrrolidone (NMP) was added and stirred thoroughly to ensure the formation of a uniform slurry; the slurry was evenly coated on aluminum foil using a coater and dried at 60 °C for 24 h. After drying, the aluminum foil was cut into circular electrodes using a slicer to obtain the desired electrode.
[0045] 3. Battery Assembly
[0046] Before assembly, all battery-related components were prepared, and CR2023 button cells were selected as the battery model. Commercial metal lithium sheets with a diameter of 16 mm were used as electrodes, and the electrolyte consisted of a DOL / DME mixture of 1 wt% LiNO3 and 1 M LiTFSI, where the volume fraction of DOL / DME was 1:1. The prepared modified diaphragm was cut into diaphragm discs with a diameter of 16 mm.
[0047] The assembly of button cells must be carried out in an argon glove box to ensure that the moisture and oxygen content in the glove box are less than 1 ppm. The assembly steps are as follows: first, place the prepared sulfur cathode material into the cathode shell; then drip an appropriate amount of electrolyte on the surface of the sulfur cathode, with a molar ratio of 24 μL·mg to sulfur. -1 . Next, add the cut diaphragm, and drip 40 μL of electrolyte on it again, and then put in the metal lithium sheet. In addition, add stainless steel gaskets, springs and negative electrode shells. Finally, use a button battery packaging machine for packaging. After packaging, let it stand for 24 hours for subsequent testing.
[0048] Example 1
[0049] Weigh 18 mg of 3,3'-((1E,1'E)-(ethane-1,2-diylbis(azoethylene))bis(methaneethylene))bis(4-hydroxybenzaldehyde) (Salen) and 1,3,5-tris(4-aminophenyl)-1,3,5-triazine (TAPT, 14 mg) into a 5 ml Pyrex tube, add solvent 1,2-dichlorobenzene (0.5 ml) and mesitylene (0.5 ml) into the Pyrex tube, treat under ultrasonic for 5 min to make it uniformly dispersed, then add acetic acid aqueous solution (6 M 0.2 ml), continue ultrasonic oscillation for 5 min, then degas in a liquid nitrogen bath using freeze pump thaw technology for three cycles, seal the tube under vacuum, and react in an oven at 120 °C for 120 h. After the reaction is completed and cooled to room temperature, the light red solid is washed 3 times with THF and vacuum dried at 100 °C for 10 h under dynamic vacuum. Salen-TAPT-COF was obtained as a light red powder with a yield of 72.3%.
[0050] Example 2
[0051] Weigh 19 mg of 3,3'-((1E,1'E)-(ethane-1,2-diylbis(azoethylene))bis(methaneethylene))bis(4-hydroxybenzaldehyde) (Salen) and 1,3,5-tris(4-aminophenyl)-1,3,5-triazine (TAPT, 14 mg) into a 5 ml Pyrex tube, add solvent 1,2-dichlorobenzene (0.5 ml) and mesitylene (0.5 ml) into the Pyrex tube, treat under ultrasonic for 5 min to make it uniformly dispersed, then add acetic acid aqueous solution (6 M 0.2 ml), continue ultrasonic oscillation for 3 min, then degas in a liquid nitrogen bath using freeze pump thaw technology for three cycles, seal the tube under vacuum, and react in an oven at 100 °C for 122 h. After the reaction is completed and cooled to room temperature, the light red solid is washed 3 times with THF and vacuum dried at 90 °C for 12 h under dynamic vacuum. Salen-TAPT-COF was obtained as a light red powder with a yield of 70.2%.
[0052] Example 3
[0053] Weigh 16 mg of 3,3'-((1E,1'E)-(ethane-1,2-diylbis(azoethylene))bis(methaneethylene))bis(4-hydroxybenzaldehyde) (Salen) and 1,3,5-tris(4-aminophenyl)-1,3,5-triazine (TAPT, 14 mg) into a 5 ml Pyrex tube, add solvent 1,2-dichlorobenzene (0.5 ml) and mesitylene (0.5 ml) into the Pyrex tube, treat under ultrasonic for 5 min to make it uniformly dispersed, then add acetic acid aqueous solution (6 M 0.2 ml), continue ultrasonic oscillation for 1 min, then degas in a liquid nitrogen bath using freeze pump thaw technology for three cycles, seal the tube under vacuum, and react in an oven at 120 °C for 120 h. After the reaction is completed and cooled to room temperature, the light red solid is washed 4 times with THF and vacuum dried at 100 °C for 12 h under dynamic vacuum. Salen-TAPT-COF was obtained as a light red powder with a yield of 68.3%.
[0054] Example 4
[0055] Synthesis of Salen-TAPT-COF / PP separator
[0056] The Salen-TAPT-COF synthesized in Example 1 was placed in a ball mill and fully ground for 30 minutes to obtain fine COF powder. The ground COF was then mixed with Ketjen black and PVDF in a mass ratio of 7:2:1 and ball-milled again for 1 hour to fully mix. Finally, 1-methyl-2-pyrrolidone (NMP) was added and wet-milled for 30 minutes to obtain a slurry. A PP diaphragm and a 40-micron coater were prepared, and the slurry was evenly coated on the surface of the diaphragm. The slurry was placed in a vacuum oven at 50°C and dried for 24 hours to obtain a Salen-TAPT-COF / PP lithium-sulfur battery diaphragm.
[0057] Example 5
[0058] Synthesis of Salen-TAPT-COF / PP separator
[0059] The Salen-TAPT-COF synthesized in Example 1 was put into a ball mill and fully ground for 30 minutes to obtain fine COF powder. The ground COF was then mixed with Ketjen black and PVDF in a ratio of 7:2:1, and ball milled again for 1.5 hours to fully mix. Finally, 1-methyl-2-pyrrolidone (NMP) was added and wet-milled for 20 minutes to obtain slurry. A PP diaphragm and a 40-micron coater were prepared, and the slurry was evenly coated on the surface of the diaphragm, and dried in a vacuum oven at 60°C for 20 hours to obtain a Salen-TAPT-COF / PP lithium-sulfur battery diaphragm.
[0060] Comparative Example 1
[0061] Weigh Salen (18 mg) and 1,3,5-tris(4-aminophenyl)-1,3,5-triazine (TAPT, 14 mg) into a 5 ml Pyrex tube, add solvent 1,2-dichlorobenzene (0.5 ml) and mesitylene (0.5 ml) into the Pyrex tube, treat under ultrasonic for 5 min to make it evenly dispersed, and then add acetic acid aqueous solution (3 M 0.2 ml). Then, degas three cycles in a liquid nitrogen bath using freeze pump thawing technology, seal the tube under vacuum, and react in an oven at 120 °C for 120 h. After the reaction is completed and cooled to room temperature, the light red solid is washed 3 times with THF and vacuum dried at 100 °C for 12 h under dynamic vacuum to obtain a light red powder sample. The PXRD pattern is shown in the following figure. Figure 6 shown.
[0062] Comparative Example 2
[0063] Weigh Salen (18 mg) and 1,3,5-tris(4-aminophenyl)-1,3,5-triazine (TAPT, 14 mg) into a 5 ml Pyrex tube, add solvent 1,2-dichlorobenzene (0.5 ml) and mesitylene (0.5 ml) into the Pyrex tube, treat under ultrasonic for 5 min to make it evenly dispersed, and then add acetic acid aqueous solution (9 M 0.2 ml). Then, degas three cycles in a liquid nitrogen bath using freeze pump thawing technology, seal the tube under vacuum, and react in an oven at 120 °C for 120 h. After the reaction is completed and cooled to room temperature, the light red solid is washed 3 times with THF and vacuum dried at 100 °C for 12 h under dynamic vacuum. A light red powder sample is obtained, and the PXRD pattern is as follows Figure 7 shown.
[0064] Comparative Example 3
[0065] Weigh Salen (28 mg) and 1,3,5-tris(4-aminophenyl)-1,3,5-triazine (TAPT, 7 mg) into a 5 mL Pyrex tube, add solvent 1,2-dichlorobenzene (0.5 ml) and mesitylene (0.5 ml) into the Pyrex tube, treat it under ultrasonic for 5 min to make it evenly dispersed, and then add acetic acid aqueous solution (6 M 0.2 ml). Then, degas three cycles in a liquid nitrogen bath using freeze pump thawing technology, seal the tube under vacuum, and react in an oven at 120 °C for 120 h. After the reaction is completed and cooled to room temperature, the light red solid is washed 3 times with THF and vacuum dried at 100 °C for 12 h under dynamic vacuum. A light red powder sample is obtained with a yield of 50%. The PXRD pattern is as follows Figure 8 shown.
[0066] It can be seen from the PXRD patterns of the samples obtained in Comparative Examples 1-3 that changing the addition ratio of Salen and 1,3,5-tris(4-aminophenyl)-1,3,5-triazine or changing the concentration of the acetic acid aqueous solution after the mixed monomers are added to the mixed solvent will have a great impact on whether Salen-TAPT-COF can be synthesized. That is, only under the conditions of the monomer addition ratio and acetic acid concentration specified in the present application can a higher yield of Salen-TAPT-COF be obtained.
[0067] The powder X-ray diffraction pattern (XRD) obtained in Example 1 is as follows: Figure 2As shown in the figure, the crystal structure of Salen-TAPT-COF was analyzed. There is a main peak at 4.1° and small peaks at 12.5, 15.2 and 25.7°, which are located at (100), (200), (011) and (400) planes, respectively. This shows that Salen-TAPT-COF material has good crystallinity. The crystal structure of Salen-TAPT-COF was analyzed by Fourier transform infrared spectroscopy (FT-IR) at 400-4000 cm -1 Analysis of the structure of Salen-TAPT-COF in the wavelength range ( Figure 2 b) Compared with the corresponding amino and aldehyde monomers, the FT-IR spectrum of Salen-TAPT-COF shows that Salen-TAPT-COF has a -1 The characteristic peak of aldehyde-HC=O stretching vibration at 3319-3208 cm -1 The characteristic peak of N-H stretching at 1622 cm -1 The new -C=N- appeared at the position of Salen-TAPT-COF, which confirmed the successful construction of Salen-TAPT-COF. 13 C CP / MAS NMR measurements to confirm the formation of the imine bond ( Figure 2 c) Salen-TAPT-COF has a peak around 160 ppm and is assigned to the carbon in the imine bond of the aldehyde-amine condensation. In addition, the inherent imine bond of the Salen monomer is 157 ppm in Salen-TAPT-COF and 163 ppm in -OH. Salen-TAPT-COF has a characteristic peak at 169 ppm, which is due to the -C=N- of the triazine ring. The thermal stability of Salen-TAPT-COF was analyzed using thermogravimetric analysis (TGA) experiments in a nitrogen atmosphere ( Figure 2 d). The Salen-TAPT-COF material has three main weight loss stages. First, it decomposes slightly at 0-100 °C, which is due to the evaporation of water and solvent molecules in the sample. Subsequently, rapid decomposition occurs at 100-240 °C and slow decomposition occurs at 240-800 °C. Salen-TAPT-COF retains 60% of its original mass at 800 °C, indicating that the material has good thermal stability.
[0068] Scanning electron microscopy (SEM) images show that Salen-TAPT-COF is formed by the aggregation of irregular petal-shaped particles ( Figure 3 a). The corresponding EDS element map shows that carbon, nitrogen and oxygen are evenly distributed in the sample ( Figure 3b). The synthesis of Salen-TAPT-COF was further confirmed by XPS test. The XPS fine spectrum of N 1s in Salen-TAPT-COF showed three main peaks at 402.8 eV, 399 eV and 401.3 eV, which corresponded to C-NH2 in Salen, CN of triazine ring and characteristic peak C=N of COF, respectively. These results fully demonstrated the successful synthesis of COF ( Figure 4 ).
[0069] Assembling Li-S batteries
[0070] 1. Preparation of C / S composites
[0071] The C / S composite material was prepared using the traditional melt diffusion method. First, Super-P powder and sulfur powder were mixed at a mass ratio of 2:8 and ground thoroughly in a mortar. Then, the mixture was placed in a polytetrafluoroethylene-lined reactor and heated at 155 °C for 24 h under an argon atmosphere. Finally, the product was collected after cooling to room temperature to obtain a C / S composite material.
[0072] 2. Preparation of conventional positive electrode
[0073] 80% of the active material (C / S prepared above), 10% of carbon black and 10% of PVDF were fully mixed and ground uniformly. Subsequently, 1-methyl-2-pyrrolidone (NMP) was added and stirred thoroughly to ensure the formation of a uniform slurry. The slurry was evenly coated on aluminum foil using a coater and then dried at 60 °C for 24 h. After drying, the aluminum foil was cut into circular electrodes using a slicer to obtain the desired electrode.
[0074] 3. Battery Assembly
[0075] Before assembly, prepare all battery-related components. A CR2023 button cell was selected as the battery model; a commercial lithium metal sheet with a diameter of 16 mm was used as the electrode. The electrolyte consisted of 1,3-dioxolane (DOL) and ethylene glycol dimethyl ether (DME) with a volume fraction of 1:1 as solvent, 1 wt% LiNO3 and 1 M LiTFSI as solute. The Salen-TAPT-COF / PP lithium-sulfur battery separator obtained in Example 4 was cut into a separator disc with a diameter of 16 mm.
[0076] The assembly of button cells must be carried out in an argon glove box to ensure that the moisture and oxygen content in the glove box are less than 1 ppm. The assembly steps are as follows: first, place the prepared sulfur cathode material into the cathode shell; then drip an appropriate amount of electrolyte on the surface of the sulfur cathode, with a molar ratio of 24 μL·mg to sulfur. -1. Next, add the cut diaphragm, and drip 40 μL of electrolyte on it again, and then put in the metal lithium sheet. In addition, add stainless steel gaskets, springs and negative electrode shells. Finally, use a button battery packaging machine for packaging. After packaging, let it stand for 24 hours before conducting subsequent tests.
[0077] Figure 5 To analyze the performance of polymer batteries, the electron transfer kinetics between the redox products and the electrodes was investigated by 0.1 mV·s in the potential range of 1.7 to 2.8 V. -1 The CV curves of batteries with different separators were measured at a scan rate of 1.5 Hz. The three-cycle CV curves fit well, indicating that the Salen-TAPT-COF battery has good electrochemical stability and reversibility. During the discharge process, two typical reduction peaks appeared near 2.2-2.4 V and 1.9-2.1 V, corresponding to the reduction of elemental sulfur to soluble long-chain LiPSs (Li2S n , 4 ≤ n ≤ 8) and further reduced to the final discharge product (Li2S2 / Li2S). During the charging process, the 2.3-2.5 V oxidation peak corresponds to the conversion of Li2S2 / Li2S to LiPSs and finally to elemental sulfur. At the same time, the redox peak can be clearly seen in the Salen-TAPT-COF separator battery, which indicates that the Salen-TAPT-COF separator oxidizes more polysulfides because nitrogen and oxygen doped Salen-TAPT-COF can effectively confine polysulfides and convert them into sulfur. In addition, the peak current intensity of the Salen-TAPT-COF separator battery is significantly enhanced, and the integrated area of the CV curve is increased, indicating that the Salen-TAPT-COF modified layer can effectively constrain polysulfides and improve the battery capacity. Figure 5 b shows the -1 The constant current charge-discharge curves of LSBs assembled by PP and Salen-TAPT-COF modified membranes at different current densities. Both exhibit a double-platform discharge curve and a single-platform charge curve, corresponding to the continuous reduction and reoxidation of sulfur, which is consistent with the Figure 5 The CV curve results of a are consistent. The discharge capacity of Salen-TAPT-COF modified film LSBs is 1168.6 mA·h·g -1 , which is higher than the discharge capacity of PP film battery (875.2 mA·h·g -1 ), the higher capacity indicates that the Salen-TAPT-COF modified layer can improve the utilization of lithium. -1 The rate performance of LSBs of both membranes was measured over a range of current densities. As expected, cells using the Salen-TAPT-COF modified membrane showed better scale-up performance, especially at high magnifications. Figure 5 c shows that the current density is 0.1, 0.2, 0.5, 1.0 and 2.0 A·g -1 When the specific discharge capacities of Salen-TAPT-COF modified membrane batteries were 1048.6, 878.4, 762.3, 700.9 and 641.4 mA·h·g -1 Under the same conditions, the specific discharge capacities of PP film batteries were 785.5, 638.1, 564.2, 506.3 and 400.4 mA·h·g -1 When the current density is increased from 2.0 A·g -1 Switch to 0.1 A·g -1 When the battery was modified with Salen-TAPT-COF, it maintained a peak power of 817.7 mA·h·g -1 The high reversible capacity of -1 Within the current density range, the constant current charge-discharge curve platforms corresponding to the two separator LSBs are significantly different ( Figure 5 d and 5e). The Salen-TAPT-COF separator cell exhibits a clear double discharge plateau at all current densities, even at 2.0 A·g -1 At high rates, a clear double discharge platform is still present, while the second discharge platform of the PP membrane battery has disappeared. This indicates that the significant improvement in the charge and discharge rate capability of the battery after Salen-TAPT-COF modification can be attributed to the presence of highly electronegative heteroatoms in the Salen-TAPT-COF modification layer, which improves the utilization of active materials and acts as a good physical barrier to effectively inhibit the shuttling of polysulfides. Figure 5 f is the battery at 1.0 A·g -1 After 500 cycles, the Salen-TAPT-COF modified layer battery still has a cycling performance of 577.7 mA·h·g -1 The high discharge capacity of the PP film battery was 98.6%, and the corresponding coulombic efficiency was maintained at 98.6%. In contrast, the capacity of the PP film battery after 500 cycles was only 459.3 mA·h·g -1 The capacity of the layer battery modified with Salen-TAPT-COF was well maintained, indicating that the shuttle effect of LiPSs was effectively suppressed.
[0078] The above embodiments are only partial implementation schemes of the present invention, but the protection scope of the present invention is not limited thereto. The various aspects and implementation schemes of the present invention disclosed herein are only examples of specific ways to make and use the present invention. The present invention is not limited to any limitation due to the sequence and specific operations of the embodiments. Any replacement and changes that can be easily thought of by any researcher familiar with the technical field within the technical scope disclosed by the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a two-dimensional Salen-based covalent organic framework lithium-sulfur battery separator having a high electronegative group, characterized in that: The following steps are involved: S1. Weigh Salen and 1,3,5-tris(4-aminophenyl)-1,3,5-triazine and add them to a Pyrex tube, add a mixed solvent of 1,2-dichlorobenzene and mesitylene to the Pyrex tube, treat under ultrasonication for 4-5 min, fully mix with the mixed monomers, add a catalyst acetic acid aqueous solution, and continue ultrasonication for 1-5 min; then degas for three cycles in a liquid nitrogen bath using a freeze pump thawing technique, seal the tube under vacuum and heat, cool to room temperature after heating to obtain a light red solid, wash the light red solid with THF 3-4 times, and vacuum dry under dynamic vacuum to obtain a light red powder Salen-TAPT-COF; S2. Put Salen-TAPT-COF into a ball mill and grind it for 30 min to obtain COF powder; mix COF powder, Ketjen black and PVDF and ball mill them for 1-1.5 h, and finally add 1-methyl-2-pyrrolidone for wet grinding to obtain slurry; use a coater to evenly apply the slurry on the surface of the PP diaphragm, and then vacuum dry it to obtain Salen-TAPT-COF / PP lithium-sulfur battery separator; The structural formula of the Salen is: .
2. The method for preparing a two-dimensional Salen-based covalent organic framework lithium-sulfur battery separator having a high electronegative group according to claim 1, characterized in that: The mass ratio of Salen and 1,3,5-tris(4-aminophenyl)-1,3,5-triazine in step S1 is (5-10):
7.
3. The method for preparing a two-dimensional Salen-based covalent organic framework lithium-sulfur battery separator having a high electronegative group according to claim 1, characterized in that: The volume ratio of 1,2-dichlorobenzene to mesitylene in step S1 is 1:
1.
4. The method for preparing a two-dimensional Salen-based covalent organic framework lithium-sulfur battery separator having a high electronegative group according to claim 1, characterized in that: The usage ratio of Salen and 1,2-dichlorobenzene in step S1 is (30-45) mg / ml.
5. The method for preparing a two-dimensional Salen-based covalent organic framework lithium-sulfur battery separator having a high electronegative group according to claim 1, characterized in that: The concentration of the acetic acid aqueous solution in step S1 is 6 mol / L, and the amount of the acetic acid aqueous solution used is 0.2 ml.
6. The method for preparing a two-dimensional Salen-based covalent organic framework lithium-sulfur battery separator having a high electronegative group according to claim 1, characterized in that: In step S1, the heating temperature is 100-120°C, and the heating time is 120-122 h; the vacuum drying temperature is 80-100°C, and the vacuum drying time is 10-12 h.
7. The method for preparing a two-dimensional Salen-based covalent organic framework lithium-sulfur battery separator having a high electronegative group according to claim 1, characterized in that: The mass ratio of the COF powder, Ketjen black and PVDF in step S2 is 7:2:
1.
8. The method for preparing a two-dimensional Salen-based covalent organic framework lithium-sulfur battery separator having a high electronegative group according to claim 1, characterized in that: The wet grinding time in step S2 is 20-30 min; the vacuum drying temperature is 50-60° C., and the vacuum drying time is 20-24 h.
9. A separator, prepared by the method for preparing a two-dimensional Salen-based covalent organic framework lithium-sulfur battery separator having a high electronegative group as claimed in claim 1.
10. A lithium-sulfur battery comprising the separator according to claim 9.
Citation Information
Patent Citations
High-performance sodium battery negative electrode organic polymer material
CN111944129A
Covalent organic framework material, preparation method of covalent organic framework material, lithium-sulfur battery diaphragm modified by covalent organic framework material, and preparation method and application of covalent organic framework material
CN116742277A